Community Compliance Model in Paying Zakat: An Empirical Approach - Widiyanto bin Mislan Cokrohadisumarto; Zaenudin (Türkiye İslam İktisadı Dergisi)
This study aims to build a community compliance model to pay zakat for wealth (zakatul mal) by involving variables such as faith, zakat rules comprehension, zakat socio-function comprehension, and the role of religious leaders. This study used faith as an intervening variable between zakat rule comprehension and zakat compliance as well as between zakat socio-function comprehension and zakat compliance. Based on primary data (i.e., from muzakki/zakat payers), this study was conducted using a quantitative approach (multiple linear regression) to obtain a model of zakat compliance by developing intervening variables. This study used Muslim communities in several regions of Central Java, Indonesia, as a sample. The results of this study suggest that zakat compliance can be increased through faith (believing that zakat is an obligation) and zakat socio function comprehension. Faith mediates the influence of zakat rule comprehension on compliance. Religious leaders play an important role in enhancing zakat rule comprehension and zakat socio function comprehension. This study has some limitations as it does not explore how to strengthen faith and build awareness of social care. Hence, future research should more deeply explore the appropriate and effective ways to increase people’s faith and zakat compliance.